Old Germplasm for New Needs Managing Crop Genetic Resources - Barba-Espín, Gregorio; Acosta-Motos, Jose Ramon (2022)
The impacts of climate change on crop production are already a reality in Europe and across the rest of the world. In order to mitigate these impacts, access to unexploited genetic crop diversity for the production of new varieties that can thrive in more extreme environmental conditions is of prime importance. Herein, genetic diversity should provide the raw materials for breeding and plant improvements. Despite the vast pool of resources that exist, much of the germplasm richness found in gene banks is poorly documented. To overcome the barriers between germplasm conservation and use, a complete evaluation is necessary to determine the useful diversity they contain.This Special Issue focuses on "Old Germplasm for New Needs: Managing Crop Genetic Resources". We gathered novel research, reviews, and opinion pieces covering all related topics, including germplasm evaluation, crop genetics and improvements, novel crops, phenotyping, physiological responses of inbred lines, management solutions, modeling, case studies from the field, and policy positions.